Tritrichomonas foetus: mecanismos de acción patógena - Doumecq, M.L. (2012)
Tritrichomonas foetus is a flagellate protozoan that affects cattle and causes the Bovine genital Trichomonosis. This is a sexually transmitted disease that produces infertility and abortions. The disease causes great economic losses in many countries including Argentina. The present review summarizes the information related to the mechanism of pathogenic action and virulence factors of the protozoan.